Prevalence of children living with non-biological parents and its determinants among children under 18 in Ethiopia: a multi-level mixed effect analysis - Tekeba, Berhan; Zegeye, Alebachew Ferede; Tamir, Tadesse Tarik (Frontiers in Public Health, 2024)
IntroductionThe absence of a biological parent from a child's existence had a negative impact on the child's growth, socialization, psychological wellbeing, and economic productivity. Developing nations like Ethiopia experience a huge number of orphans and family-unbounded children. But the exact figure has not been reported yet at the national level recently. Thus, this study aimed to assess the magnitudes and determinants of children living with non-biologic parents in Ethiopia.MethodsSecondary data analysis was conducted based on the demographic and health survey data conducted in Ethiopia in 2016. A total weighted sample of 41,884 children under the age of 18 from 5 years preceding the survey was included in this study. A multi-level logistic regression model was used to identify the determinants of children living with non-biologic parents. The adjusted odds ratio at 95% Cl was computed to assess the strength and significance of the association between explanatory and outcome variables. Factors with a p < 0.05 are declared statistically significant.ResultsThe prevalence of children living with non-biologic parents in Ethiopia was 17.58% (95% CI, 17.22–17.95). Being an orphan (AOR = 4.57, 95% CI: 2.40–7.25), being in first birth order (AOR = 8.22, 95% CI: 6.31–9.17), being from a household lacking formal family structure (AOR = 8.60, 95% CI: 6.20–12.30), and being from a female-headed household (AOR = 3.43, 95% CI: 2.65–4.43) were individual-level factors that were significantly associated with children living with non-biologic parents. Being a rural resident (AOR = 1.94, 95% CI: 1.23–3.08) and having a high community poverty level (AOR = 1.25, 95% CI: 1.01–1.75) were community-level determinants of children living with non-biologic parents.ConclusionAccording to this study, a significant proportion of children live with non-biological parents in Ethiopia. Thus, policymakers, health planners, and implementers need to give special attention to children from rural communities, orphans, firstborn children, and broken families. In addition, efforts shall be made to empower women and, in the long run, improve the economy of the community.